P057 Uveitis in enthesitis-related arthritis: what are the predictive factors?. (11th November 2021) - Miri, Sirine; Triki, Wafa; Ferjani, Hanene; Maatallah, Kaouther; Nsib, Dorra Ben; Kaffel, Dhia; Hamdi, Wafa
Abstract: Background: Juvenile idiopathic arthritis (JIA) is the most common rheumatic disease of childhood. Uveitis is its most common extra-articular manifestation [1]. It is a potentially sight-threatening condition with a considerable risk of morbidity. This study aimed to describe the prevalence and characteristics of JIA-related uveitis in enthesitis-related arthritis (ERA) patients. Methods: We conducted a retrospective study including 40 patients with JIA according to the classification criteria of the International League of Associations for Rheumatology (ILAR). All selected patients presented with ERA. A screening of uveitis was conducted in all patients. Clinical, radiologic and, biologic features of JIA were collected. We evaluated the association between these features and the presence of uveitis. Results: The mean age of our patients was 24 years, with a sex ratio of 3. The mean age at the onset of JIA was 11 years. Upon screening, fifteen percent of the patients had active uveitis. Nine percent of the patients presented with an acute onset of JIA. Forty-six percent had initial spinal symptoms, while 26% presented with peripheral onset. Upon examination, 4% of the patients presented with monoarthritis, 20.4% with oligoarthritis and 34.8% with polyarthritis. Thirteen percent had enthesitis. Fifty-seven percent of the patients had coxitis. Sixty-eight percent had sacroiliitis. The mean CRP and ESR levels were respectively 16 mg/l and 34. Human leucocyte antigen (HLA) B27 screening came back positive in 11% of the cases. The mean BASDAI and BASFI levels were both at 4.7. The mean MASES was 0.44. Twenty percent of the patients received NSAIDs. Eleven percent received methotrexate, 18% salazopyrine and, 5.6% biologics. A significant association was established between the presence of uveitis and a polyarticular onset of JIA ( P  = 0.036). However, no significant associations were established with the sex of patients ( P  = 0.457), age of onset ( P  = 0.828), activity of the disease as evaluated by BASDAI ( P  = 0.40) and MASES ( P  = 0.87), inflammatory markers (CRP P  = 0.946, and ESR P  = 0.662), the use of NSAIDS ( P  = 1), methotrexate ( P  = 0.318), salazopyrine ( P  = 0.170) and biologics ( P  = 1). Conclusion: In conclusion, uveitis associated with JIA is a serious and sight-threatening disease. Several factors associated with a more severe disease development have been identified [2–4]. Our study showed a significant association between the polyarticular onset of JIA and the occurrence of uveitis. Also, our study showed no significant association with male gender and HLA-B27 in children, unlike previous studies of spondyloarthritis conducted in adults [5–6]. We conclude that the screening of uveitis should be performed in all JIA patients, especially those presenting initially with polyarthritis.